EFFECT OF HARMFUL ALGAL BLOOMS IN FAR EASTERN SEAS OF RUSSIA AND NECESSITY OF DEVELOPMENT OF COUNTERMEASURES - O. G. SHEVCHENKO,; T. YU. ORLOVA, (The Bioscan, 2010)
A total of 25 red tide events were observed during 1992–2010 in the coastal waters of Far Eastern seas of Russia. No any cases of human poisoning or mass mortality of fish and shellfish were recorded. A total of 12 species caused red tides in study area during 1992 to 2010. Those species belonged to 4 taxonomic groups of phytoplankton: dinoflagellates, diatoms, raphidophytes and euglenophytes. Eleven toxic species were observed. Potentially toxic species belong to 2 groups of phytoplankton: dinoflagellates and diatoms. Diatoms of the genus Pseudo-nitzschia are known as domoic acid producing species (ASP). Five species P. pungens, P. multiseries, P. multistriata, P. pseudodelicatissima and P. calliantha were monitored in study area.Species of Dinophysis are capable of producing ocadaic acid, causing the syndrome of diarrhetic shellfish poisoning (DSP). Four species Dinophysis acuminata, D. acuta, D. fortii and D. rotundata were observed in the Far Eastern seas of Russia in 1992–2010. D. acuminata was the most common species in the study area.The genus Alexandrium of Dinoflagellates may cause the paralytic shellfish poisoning (PSP). Three potentially toxic species of the genus Alexandrium: A. tamarense, A. acatenella and A. pseudogonyaulax were observed in Russian waters in 1992–2010.